2016
DOI: 10.1037/ort0000078
|View full text |Cite
|
Sign up to set email alerts
|

Using communities that care for community child maltreatment prevention.

Abstract: The prevention of mental, emotional, and behavioral (MEB) disorders among children and adolescents is a national priority. One mode of implementing community-wide MEB prevention efforts is through evidence-based community mobilization approaches such as Communities That Care (CTC). This article provides an overview of the CTC framework and discusses the adaptation process of CTC to prevent development of MEBs through preventing child abuse and neglect and bolstering child well-being in children aged 0 to 10. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 44 publications
(62 reference statements)
0
13
0
Order By: Relevance
“…The data collection procedures, participants, and measures for each evaluation instrument are discussed below in sections dedicated to each instrument. Additional information on the CTC evaluation instruments used in this study, as well as a description of the adaptation process for these instruments for this adapted CTC approach can be found in Salazar et al (2016), as well as the publications referenced in each section. This study was determined exempt from review by the University of Washington IRB.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The data collection procedures, participants, and measures for each evaluation instrument are discussed below in sections dedicated to each instrument. Additional information on the CTC evaluation instruments used in this study, as well as a description of the adaptation process for these instruments for this adapted CTC approach can be found in Salazar et al (2016), as well as the publications referenced in each section. This study was determined exempt from review by the University of Washington IRB.…”
Section: Methodsmentioning
confidence: 99%
“…In our previous paper (Salazar et al, 2016), we presented preliminary findings from the evaluation of the Keeping Families Together adapted approach approximately 1 year into implementation, which suggested that implementation was manageable for sites (as evidenced by sites reporting high implementation fidelity and low implementation challenge ratings), and that community board functioning and community adoption of a science-based approach to prevention were comparable to that of the 12 traditional CTC trial sites at a similar point in the implementation process. The current paper aims to provide an update on site progress 3.5 years into the implementation process.…”
Section: Current Studymentioning
confidence: 98%
See 2 more Smart Citations
“…As noted previously, eight of the included articles described or evaluated an intervention designed to increase community support for vulnerable families. The most common of which were the Strong Communities initiative (Hashima et al, 2008;Haski-Leventhal et al, 2008;Kimbrough-Melton & Melton, 2015;McLeigh, Katz, Davidson-Arad, & Ben-Arieh, 2017;McLeigh et al, 2015) and Keeping Families Together, adapted from Communities that Care (Salazar et al, 2016;Salazar et al, 2019). One article provided an overview of five different programs, three of which target community social norms (rather than parenting practices) (Daro & Dodge, 2009).…”
Section: Rq3: What Types Of Interventions and Campaigns Have Been Sho...mentioning
confidence: 99%